Mechanism of recovery from acute virus infection: treatment of lymphocytic choriomeningitis virus-infected mice with monoclonal antibodies reveals that Lyt-2+ T lymphocytes mediate clearance of virus and regulate the antiviral antibody response. - Moskophidis, D (1987)
After intravenous infection of mice, lymphocytic choriomeningitis virus multiplied in spleens and livers, attaining highest concentrations on days 4 to 6. The subsequent clearance was as rapid, and 8 to 10 days after inoculation, infectivity was usually below detectability. During the effector phase of virus elimination, both cytotoxic T-cell (CTL) activity and the number of cells producing antiviral antibodies were high. Monoclonal antibodies directed against T lymphocytes and T-lymphocyte subsets were inoculated once intravenously 5, 6, or 7 days after infection of the animals, and the effects on antiviral immune responses, as well as on elimination of virus from the organs, were determined. Treatment with anti-Thy-1 and anti-Lyt-2 antibodies blocked elimination of the virus and profoundly diminished the activity of spleen CTLs but reduced the antibody response partially (anti-Thy-1) or increased it (anti-Lyt-2). In contrast, treatment with the anti-L3T4 antibody had essentially no effect on either virus elimination or CTL response but abolished antibody production. We conclude that Lyt-2+ (cytotoxic-suppressive) T lymphocytes are needed for elimination of the virus and also regulate the humoral response but that antiviral antibodies are not essential for control of the infection.